2022
DOI: 10.1371/journal.pgen.1010260
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for Li-Fraumeni-Like Syndrome with cardiac angiosarcomas associated to POT1 mutations

Abstract: The shelterin protein POT1 has been found mutated in many different familial and sporadic cancers, however, no mouse models to understand the pathobiology of these mutations have been developed so far. To address the molecular mechanisms underlying the tumorigenic effects of POT1 mutant proteins in humans, we have generated a mouse model for the human POT1R117C mutation found in Li-Fraumeni-Like families with cases of cardiac angiosarcoma by introducing this mutation in the Pot1a endogenous locus, knock-in for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In 2022, a further convincing study observed the same effect on TL for this variant and the development of angiosarcomas in the knock-in mice model [32].…”
Section: Sarcomamentioning
confidence: 83%
“…In 2022, a further convincing study observed the same effect on TL for this variant and the development of angiosarcomas in the knock-in mice model [32].…”
Section: Sarcomamentioning
confidence: 83%